"Cyt/Nuc, " a Customizable and Documenting ImageJ Macro for Evaluation of Protein Distributions Between Cytosol and Nucleus. Issue 5 (9th February 2018) - Grune, Tilman; Kehm, Richard; Höhn, Annika; Jung, Tobias
Abstract : Large amounts of data from multi‐channel, high resolution, fluorescence microscopic images require tools that provide easy, customizable, and reproducible high‐throughput analysis. The freeware "ImageJ" has become one of the standard tools for scientific image analysis. Since ImageJ offers recording of "macros, " even a complex multi‐step process can be easily applied fully automated to large numbers of images, saving both time and reducing human subjective evaluation. In this work, we present "Cyt/Nuc, " an ImageJ macro, able to recognize and to compare the nuclear and cytosolic areas of tissue samples, in order to investigate distributions of immunostained proteins between both compartments, while it documents in detail the whole process of evaluation and pattern recognition. As practical example, the redistribution of the 20S proteasome, the main intracellular protease in mammalian cells, is investigated in NZO‐mouse liver after feeding the animals different diets. A significant shift in proteasomal distribution between cytosol and nucleus in response to metabolic stress was revealed using "Cyt/Nuc" via automatized quantification of thousands of nuclei within minutes. "Cyt/Nuc" is easy to use and highly customizable, matches the precision of careful manual evaluation and bears the potential for quick detection of any shift in intracellular protein distribution. Abstract : Here, "Cyt/Nuc, " a highly customizable and documenting, "ImageJ, " macro is presented for evaluation of protein distributions between nucleus and cytosol in fluorescence microscopic images.